Consumer adoption of on-demand digital platforms: An integrated model - Lim, Tze Yin; Lim, Bibiana Chiu Yiong; Leong, Choi Meng; Phang Ing @ Grace; Weng, Heng Foong (Wiley Periodicals, LLC, 2023)
On-demand digital platforms are omnipresent in the contemporary marketplace of the digital era. The purpose of this study was to assess the factors influencing consumers’ intention to adopt on-demand digital platforms in the context of a developing country. Based on a modified integration of the unified theory of acceptance and use of technology (UTAUT) and the social influence theory, this study contended that electronic word-of-mouth (eWOM) about on-demand digital platforms shapes consumers’ perceived risk and subjective norms, which, along with the other elements of UTAUT, influence their intention to use OnDemand digital platforms. A self-administered questionnaire was developed and distributed online, yielding a total of 226 responses, which were analyzed using partial least squares structural equation modelling. The findings revealed that performance expectancy, effort expectancy, subjective norms, and perceived risk significantly affect consumers’ intention, wherein eWOM reduces perceived risk and shapes subjective norms to adopt on-demand digital platforms. Therefore, this study contributes to the literature on consumer adoption of new-age digital products, and in this case, on-demand digital platforms, with implications for theory and practice in this space.